Learning Strategies During Pandemic Covid-19 at SMK Muhammadiyah 1 Mojokerto - Nurmansyah Eryka Putri (Proceedings of The ICECRS, 2021)
Covid-19 has disrupted the learning process. Hence the need for solutions to continue the teaching process, online learning is one of the alternatives that can address this problem. This aim to describe stragegi learning in SMK Muhammadiyah 1 Mojokerto during pandemic covid-19 to get an idea of the implementation of online learning, the study sample is observation. Data collection's done with interviews. Online learning has flexibility in performance and is able to encourage self-awareness and motivate students to be more active in learning. Long-distance fishing encourages social distancing behavior and minimizes student presence so as to reduce covid-19 spread potential in the school ward. Weak student supervision, a lack of signal strength in remote areas, and a high cost of Internet credit in online learning. Increased self-reliance is learning, interest, motivation, courage to express ideas and other possible questions of online learning.